• Matéria: Matemática
  • Autor: romanarodio
  • Perguntado 7 anos atrás

X - 11 = 36

2X - 1 = -7

- 3X + 2 = - 7

Respostas

respondido por: Danielsantos1232
1

Resposta:


Explicação passo-a-passo:

1) x-11 = 36

x = 36 + 11

x = 47

2) 2x - 1 = -7

2x = -7 + 1

2x = -6

x = -6/2 = -3

3) -3x + 2 = -7

-3x = -7 -2

-3x = - 9

x = -9/-3

x = 3


respondido por: albertrieben
0

a)

x - 11 = 36

x = 36 + 11 = 47

b)

2x - 1 = -7

2x = -7 + 1 = -6

x = -3

c)

- x + 2 = - 7

-3x = -7 - 2= -9

x = 3



Perguntas similares